Analysis of the role of viral encephalitis in the development of epileptic seizures and epilepsy - Litovchenko, Tetyana; Bilchenko, Oleksandr; Malakhov, Vladimir; Dubenko, Olga; Sukhonosova, Olga; Bokatuieva, Viktoriia; Markova, Marianna; Nikonov, Vadym (ScienceRise: Medical Science, 2020)
The aim – to determine the role of viral lesions of the central nervous system (CNS) in the development of epileptic seizures and epilepsy. Materials and methods: analysis of scientific literature data. The review discusses the role of non-epidemic viral encephalitis and human immunodeficiency virus in the development of acute epileptic seizures and epilepsy; epidemiological data and risk factors. Results. Viral infections are often complicated by acute (early) epileptic seizures and causes the risk of further epilepsy. The mechanisms of development of early and late seizures differ. Except herpetic encephalitis, in which risk of epilepsy in early seizures is up to 60 %, the risk of late seizures in other viral encephalitis hasn't been determined. Timely treatment of viral infections and early seizures reduces the risk of epilepsy. Treatment of epilepsy with infectious lesions of the central nervous system and other types of symptomatic epilepsy is similar, and the antiepileptic drug is determined by the semiology of seizures. The interaction between it and anti-infective drugs can change the concentration in the blood of each of them, which will lead to reduced effectiveness or toxicity. This is especially important for individuals with human immunodeficiency virus infection in whom antiretroviral drugs have significant interactions with antiepileptic drugs. Since epileptic activity of the brain is associated with the severity and complications of the underlying infection, early aggressive therapy prevents the development of late seizures and epilepsy. Conclusions. CNS infections account for 15 % of all newly diagnosed symptomatic epileptic seizures. The 20-year risk of unprovoked seizures and epilepsy after CNS infections ranges from 2.4 % to 22 %. The risk depends on the etiology, location of the lesion and the severity; it is high in herpes-associated encephalitis